Development of a glial cell-derived neurotrophic factor-releasing artificial dura for neural tissue engineering applications. Issue 40 (18th August 2015) - Mohtaram, N. K.; Ko, J.; Agbay, A.; Rattray, D.; Neill, P. O.; Rajwani, A.; Vasandani, R.; Thu, H. L.; Jun, M. B. G.; Willerth, S. M.
Abstract : Develop a scaffold consisting of aligned, drug releasing nanofiber to serve as a replacement for damaged dura mater. Abstract : Encapsulated electrospun nanofibers can serve as an artificial dura mater, the membrane that surrounds the brain and spinal cord, due to their desirable drug delivery properties. Such nanofiber scaffolds can be used to deliver drugs such as glial cell-derived neurotrophic factor (GDNF). GDNF promotes the survival of both dopaminergic and motor neurons, making it an important target for treatment of central nervous system injuries and disorders. This work focuses on designing a novel class of encapsulated poly(ε-caprolactone) (PCL) nanofiber scaffolds with different topographies (random and aligned) that generate controlled release of GDNF to potentially serve as a suitable substitute for the dura mater during neurosurgical procedures. Random and aligned scaffolds fabricated using solution electrospinning were characterized for their physical properties and their ability to release GDNF over one month. GDNF bioactivity was confirmed using a PC12 cell assay with the highest concentrations of released GDNF (∼341 ng mL −1 GDNF) inducing the highest levels of neurite extension (∼556 μm). To test the cytocompatibility of aligned GDNF encapsulated PCL nanofibers, we successfully seeded neural progenitors derived from human induced pluripotent stem cells (hiPSCs) onto the scaffolds where they survived and differentiated into neurons. Overall, this research demonstrates the potential of such substrates to act as artificial dura while delivering bioactive GDNF in a controlled fashion. These scaffolds also support the culture and differentiation of hiPSC-derived neural progenitors, suggesting their biocompatibility with the cells of the central nervous system.